Using Psychological Self-Regulation to Reduce Stress in Professional Activities - Sergeevna, Treinis Ekaterina; Dmitrievna, Lukashevich Olga; Mikhailovna, Khromova Elena (European Journal of Life Safety and Stability (2660-9630), 2022)
The importance of mastering the mechanisms of mental self-regulation in professional activity, especially by operators of complex technical objects, is substantiated. The essence of professional stress, psychophysiological and mental self-regulation is revealed